Microcatheter selective injection technique using ultra low contrast for percutaneous coronary intervention in patients with previous acute kidney injury: a case report - Mangkuanom, Arwin Saleh; Satrio, Revan; Mendel, Brian; Firman, Doni; Iryuza, Nanda; Alkatiri, Amir Aziz (Frontiers in Cardiovascular Medicine, 2025)
BackgroundContrast-induced nephropathy (CIN) is a risk in angiographic procedures, especially for patients with acute kidney injury (AKI). To mitigate this risk, ultra-low contrast percutaneous coronary intervention (ULC-PCI) has been developed, which minimizes the use of contrast agents.Case summaryA 54-year-old woman with a history of AKI from a prior percutaneous coronary intervention (PCI) was found to have coronary artery disease with three vessels disease and chronic total occlusion in the right coronary artery. To minimize contrast use, she underwent ultra-low contrast PCI using the “microcatheter injection” technique, with only 5 cc of contrast used during the procedure. At one-year follow-up, the patient's LVEF improved from 33% to 56%, symptoms resolved with no chest pain. Her estimated glomerular filtration rate (eGFR) showed no significant decrease, since serum creatinine increased slightly from 1.59 mg/dl to 1.61 mg/dl. and eGFR decreased from 39 to 38 ml/min/1.73 m2 in 72 h.ConclusionsThe microcatheter injection technique may serve as a viable strategy for percutaneous coronary intervention (PCI) in patients with eGFR < 30 ml/min/1.73 m2 or history of contrast-induced nephropathy.